Aortico-Left Atrial Fistula: A Rare Complication of Bioprosthetic Aortic Valve Endocarditis Secondary to Enterococcus faecalis - Abhinav Agrawal; Martin Miguel Amor; Deepa Iyer; Manan Parikh; Marc Cohen (Case Reports in Cardiology)
Paravalvular aortic root abscess with intracardiac fistula formation is an exceedingly rare complication of infective endocarditis. This condition is even more rarely encountered in patients with bioprosthetic valve endocarditis. We report an unusual case of a 68-year-old Bosnian female with a bioprosthetic aortic valve, who developed an extensive aortic root abscess, complicated by an aortico-left atrial intracardiac fistula. This case illustrates that a high index of suspicion, prompt diagnosis by echocardiography, proper antibiotic therapy, and early surgical intervention are crucial to improving treatment outcomes for this rare condition.